2018
DOI: 10.1002/tox.22657
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic effects of Terminalia catappa leaf extracts on cervical cancer through the inhibition of matrix metalloprotein‐9 and MAPK pathway

Abstract: The effects of Terminalia catappa leaf extracts (TCE) have been widely investigated, including its antioxidative, anti-inflammatory, and antidiabetic activity, as well as its antimetastatic effects on several types of human cancer. However, no study has examined the antimetastatic potential of TCE in cervical cancer cells. This study aimed to elucidate the potential antimetastatic properties of ethanol extracts of Terminalia catappa in 12-O-tetradecanoylphorbol-13-acetate treated human cervical cancer cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…34 The inhibition of MMP-9 expression effects of Terminalia catappa leaf extracts on cervical cancer cells was also reported. 27 Thus, MMP-9 could be a potential therapeutic target for cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The inhibition of MMP-9 expression effects of Terminalia catappa leaf extracts on cervical cancer cells was also reported. 27 Thus, MMP-9 could be a potential therapeutic target for cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have speculated that the MAPK signaling is known to regulate MMP-9 expression and play a vital role in cancer metastasis. [27][28][29] Thus, western blotting was used to investigate the effects of DNE on the expression of the MAPK pathway in HeLa cells. The results revealed that DNE significantly diminished the TPA-induced phosphorylation of ERK1/2 ( Figure 4A).…”
Section: Effects Of Dne On the Mapk Pathway In Hela Cellsmentioning
confidence: 99%
“…In the process of degradation, large amounts of vascular endothelial growth factors stored in the extracellular matrix can be released to induce tumor angiogenesis and provide the necessary nutritional basis and pathway for tumor cell invasion [25]. MMP-9, also known as Gelatinase B, can degrade and destroy extracellular matrix and basement membrane near the surface of tumor cells, release a large number of growth promoting factors, and make tumor cells invade the surrounding tissues along the missing basement membrane, promoting the invasion and metastasis of tumor cells [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Also, leaf ethanol extracts of T. catappa L. from Taiwan was reported by Lee et al. (2019) , who used HeLa and SiHa cervical cancer cell lines to test its antiproliferative effect.…”
Section: Pharmacological Effects Of Active Constituents From mentioning
confidence: 99%
“…It was shown that Terminalia sp. extracts have low cytotoxicity and suppress TPA-induced migration and invasion through the inhibition of MMP-9 and ERK1/2 phosphorylation in the cell lines in a dose-dependent manner ( Lee et al., 2019 ). Likewise, water extracts from T. chebula Retz.…”
Section: Pharmacological Effects Of Active Constituents From mentioning
confidence: 99%